CLINICAL AND ECONOMICAL ASPECTS OF NOVEL APPROACHES TO THE TREATMENT OF CHRONIC HEART FAILURE DECOMPENSATION - S. K. Zyryanov; G. P. Arutyunov (Российский кардиологический журнал, 2015)
Aim. To study the changes in expenses for the usage of the novel medication serelaxine in treatment of decompensated chronic heart failure.Material and methods. At the core of study — buit-up Mark model that takes into consideration two scenarios of the disease course in patients with decompensated CHF: the usage of standard treatment and standard treatment with serelaxine add-on. Probability of the shift from one condition to another for both groups is calculated based on the results of international clinical trials Pre-Relax-AHF and Relax-AHF as by the data of Russian registry ORAKUL-RF. The sources of information on the price of the resources involved were open. As the whole data was not completely comparable in the build-up of the model we made some presuppositions: time hoirizon of observation — 1 year; results of Pre- Relax-AHF and Relax-AHF extrapolated to 1 year; serelaxine was prescribed only in the first episode of CHF decompensation therapy; mean rate of deaths in decompensated CHF in all age groups was the same; dynamics of mortality inside the each time cutoff (1 month, 2-6 months, 7-12 months) was similar. Except of the direct medical expenses the followinf were also calculated: amount of undercollected GDP as a result of economically active patients death; expenses for repeated hospitalizations; expenses for emergency calls; expenses for the treatment of heart failure exacerbation; size of undercollected GDP as a result of no-show of the patient at workplace for economically active patients.Results. Expenses for hospitalization and emergency calls in serelaxine group due to lower rate of hospitalizations were almost two times lower comparing to the standard therapy group: 40,9 and 19,3 mln. rubles per 1000 patients, respectively. While using serelaxine the GDP losses due to temporary disability (the size of undercollected GDP) in the group of 1000 patients decreased by 11,5 mln. rubles, or 50%, and if to include the death related losses — by 29,3 mln. rubles (36,5%) by 1 year. Additional expenses for drug therapy of heart failure by serelaxine are compensated by the decrease of general expenses (including additional therapy by serelaxine) by 7,4-28% in patients of economically active age with decompensated CHF.Conclusion. Serelaxine as drug with the main clinical properties as the decrease of general and cardiovascular mortality, positive influence on the level of nephrologic complications and hospitalizations, shows economical superiority in the management of economically active age patients. Currently the use of serelaxine in patients with decompensated CHF might optimize the expenses of Russian healthcare budget related to the treatment of patients with this condition.